Association between Diastolic Dysfunction with Inflammation and Oxidative Stress in Females ob/ob Mice - Sartori, Michelle; Conti, Filipe F.; Dias, Danielle da Silva; Santos, Fernando dos; Machi, Jacqueline F.; Palomino, Zaira; Casarini, Dulce E.; Rodrigues, Bruno; De Angelis, Kátia; Irigoyen, Maria-Claudia (Frontiers in Physiology, 2017)
To evaluate autonomic and cardiovascular function, as well as inflammatory and oxidative stress markers in ob/ob female mice. Methods: Metabolic parameters, cardiac function, arterial pressure (AP), autonomic, hormonal, inflammatory and oxidative stress markers were evaluated in 12-weeks female wild-type (WT group) and ob/ob mice (OB group). Results: OB animals showed increased body weight, blood glucose, and triglyceride levels, along with glucose intolerance, when compared to WT animals. Ejection fraction and AP were similar between groups; however, the OB group presented diastolic dysfunction, as well as an impairment on myocardial performance index. Moreover, the OB group exhibited important autonomic dysfunction and baroreflex sensitivity impairment, when compared to WT group. OB group showed increased Angiotensin II levels in heart and renal tissues; decreased adiponectin and increased inflammatory markers in adipose tissue and spleen. Additionally, OB mice presented a higher damage to proteins and lipoperoxidation and lower activity of antioxidant enzymes in kidney and heart. Correlations were found between autonomic dysfunction with angiotensin II and inflammatory mediators, as well as between inflammation and oxidative stress. Conclusions: Our results showed that female adult ob/ob mice presented discrete diastolic dysfunction accompanied by autonomic disorder, which is associated with inflammation and oxidative stress in these animals.